Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1039/c9fo01334b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of theabrownin on serum metabolites and gut microbiome in rats with a high-sugar diet

Abstract: In a high sugar diet mode, TB reduced the body weight and TG and improved HOMA-IR mainly by targeting the gut microbiota. A strong correlation between cecal microorganisms and serum metabolites, obesity and HOMA-IR was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
52
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 64 publications
4
52
1
Order By: Relevance
“…In particular, the Bacteroides genus has been reported as the most predominant member of the cecal microbiota of Bermuda free-range broilers. In this study, the genus Bacteroides was the positive bacterium in the jejunum and cecum, which is in line with the previous finding that a higher number of Bacteroides enables larger efficiency of gut microbiota in extracting energy from the diet ( Yue et al, 2019 ). Of interest, in our findings, the genus Lactobacillus was the second leading bacterium in the jejunum.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the Bacteroides genus has been reported as the most predominant member of the cecal microbiota of Bermuda free-range broilers. In this study, the genus Bacteroides was the positive bacterium in the jejunum and cecum, which is in line with the previous finding that a higher number of Bacteroides enables larger efficiency of gut microbiota in extracting energy from the diet ( Yue et al, 2019 ). Of interest, in our findings, the genus Lactobacillus was the second leading bacterium in the jejunum.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that the positively significant correlations between Alloprevotella and SCFAs became insignificant with the reduction of Alloprevotella caused by orlistat. Animal studies found that both the HFD and high-sucrose diet reduced the abundance of Alloprevotella , while the combination of the abrownin and the high-sugar diet promoted the reproduction of Alloprevotella ( Kong et al, 2019 ; Yue et al, 2019 ). These results indicate that the colonic accumulation of dietary fat might result in the enrichment of the opportunistic pathogens with the depletion of potential beneficial microbes related to obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The increased abundance of Lactobacillus murinus correlates with higher serum levels of primary CA and secondary deoxycholic bile acid. Therefore, compared to a WD, an n-6HFD rich in LA may alter the relative abundance of Lactobacillus spp., favoring the overgrowth of Lactobacillus murinus [44].…”
Section: Discussionmentioning
confidence: 99%